PUBLIC SERVICE QUALITY AS AN INFORMAL INSTRUMENT OF POLITICAL EDUCATION: IMPLICATIONS FOR PUBLIC INSTITUTIONAL TRUST - Enjang Kusnadi (Journal of International Islamic Law, Human Right and Public Policy, 2026)
Abstract Political education in Indonesia is often reduced to electoral participation, ignoring the crucial role of citizens' daily interactions with the bureaucracy. This study aims to analyze how the quality of administrative services transforms into an informal political education tool that affects the level of institutional trust at the local level. Employing a descriptive qualitative approach through a case study in Cimaja Village, Sukabumi Regency, data were collected using a rapid assessment technique consisting of observations and in-depth interviews with residents and village apparatus. The results show that responsive, equal, and transparent public services by street-level bureaucracy empirically function as a democratic "classroom". Fair administrative interactions can reduce administrative burdens, build awareness of citizenship rights, and reduce political cynicism among the public. Furthermore, the quality of basic services is proven to reduce this cynicism and build autonomous institutional trust that encourages citizens' active participation in village development. This study concludes that public administration and political science cannot be rigidly separated at the level of local governance, where public service performance is an effective political education instrument. As a practical implication, it is recommended that local democracy evaluations integrate basic public service satisfaction.